Brucella induces heme oxygenase‐1 expression to promote its infection. Issue 5 (5th January 2022) - Hu, Hai; Tian, Mingxing; Yin, Yi; Zuo, Dong; Guan, Xiang; Ding, Chan; Yu, Shengqing
Abstract: Brucellosis is a zoonotic and contagious infectious disease caused by Brucella spp, which causes substantial economic losses to animal husbandry and leads to severe public health problems. Brucella have evolved multiple strategies to escape host immunity and survive within host cells. Elucidating the immune evasion strategies during Brucella infection will facilitate the control of brucellosis. The host enzyme, heme oxygenase‐1 (HO‐1), is a multifunctional protein that functions during inflammatory diseases and microbial infections. However, how HO‐1 functions during Brucella infection is rarely studied. In this study, we evaluated the role of HO‐1 during Brucella infection. We found that Brucella infection induced HO‐1 expression in macrophages. We further showed that HO‐1 was regulated by PI3K, AMPK kinase, and nuclear erythroid‐related factor 2 (Nrf2) in macrophages. Interestingly, knocking out HO‐1 or inhibiting the activity of HO‐1 significantly decreased Brucella intracellular growth. Inducing the expression of HO‐1 by treatment with CoPP promoted Brucella intracellular growth. Mechanistic analyses indicated that the effect of HO‐1 was not meditated by HO‐1 metabolites, but by decreasing the production of reactive oxygen species (ROS), TNF‐α, and IL‐1β. Moreover, Brucella induced HO‐1 expression in bone marrow‐derived macrophages (BMDMs) and mice. When the expression of HO‐1 was knocked down in BMDMs, the intracellular survival of Brucella was reduced. Furthermore, the induction of HO‐1 by CoPP significantly increased bacterial loads in vivo. Thus, we demonstrated that Brucella induced HO‐1 expression to promote its survival and growth in vitro and in vivo. This study also identified HO‐1 as a novel innate immune evasion factor during Brucella infection.